Die assyrische Deportationspolitik unter Sargon II und die Midianiternot im Richterbuch - Staszak, Martin (Biblische Zeitschrift, 2020)
This article assumes that the so called misery that Midian brought to Israel (Jdg 6:1-6) refers to the activities of deported Arabs who were settled in Samaria by the Assyrian king Sargon II in 715 BCE, in order to pacify the Arabs. Assyrian texts show that the Assyrian empire had to struggle both with raids by Arabs against cities and their inhabitants and with difficulties caused by deported people. A probably multilayered pre-deuteronomistic redaction (ca. 700) that formed a cycle of narratives (Ehud, Deborah and Baraq, Gideon) transfered a local problem to the whole country of Israel and called the Arabs Midianites because of their common origin in Northern Arabia. It is possible that the Assyrians tolerated the raids by the Arabs in order to suppress the defeated Samarian population and to garner some profit from the Arabs.